2018
DOI: 10.1139/cjp-2017-0185
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal analysis of students’ motivational characteristics in introductory physics courses: Gender differences

Abstract: The lack of diversity and the under-performance of underrepresented students in STEM courses have been the focus of researchers in the last decade. In particular, many hypotheses have been put forth for the reasons for the under-representation and under-performance of women in physics. Here, we present a framework for helping all students learn in science courses that takes into account four factors: (1) the characteristics of instruction and learning tools, (2) student characteristics, (3) implementation of i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
101
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

5
5

Authors

Journals

citations
Cited by 89 publications
(114 citation statements)
references
References 102 publications
5
101
0
Order By: Relevance
“…Unfortunately, several studies have shown that female students have significantly lower self-efficacy than male students in STEM-related domains [23,53,54] including in mathematics, engineering [14,24,55], and computer science [56,57]. In physics, female students report significantly lower self-efficacy than male students [58][59][60][61][62], even in interactive engagement courses [60] and even if female students had received prior physics instruction in high school [61]. Furthermore, female students experience a decline in self-efficacy throughout their engineering education at college [55].…”
Section: A Underrepresentation Of Women In Stem Fieldsmentioning
confidence: 99%
“…Unfortunately, several studies have shown that female students have significantly lower self-efficacy than male students in STEM-related domains [23,53,54] including in mathematics, engineering [14,24,55], and computer science [56,57]. In physics, female students report significantly lower self-efficacy than male students [58][59][60][61][62], even in interactive engagement courses [60] and even if female students had received prior physics instruction in high school [61]. Furthermore, female students experience a decline in self-efficacy throughout their engineering education at college [55].…”
Section: A Underrepresentation Of Women In Stem Fieldsmentioning
confidence: 99%
“…We then created a survey to cover the core aspects of each construct but with a goal to minimize total survey length, adapting questions from other well-validated surveys [7,8,[10][11][12][13][14][15]. The final version of the survey has 29 Likert-scale items.…”
Section: Methodsmentioning
confidence: 99%
“…Since there have been relatively few longitudinal studies focusing on underrepresented racial/ethnic minority students' self-efficacy and intrinsic interest in physics [11], we investigated students' motivational characteristics at three time points during a two-semester algebra-based and calculus-based introductory physics course sequence. The findings can be a stepping stone to developing and implementing learning tools in order to help all students succeed in physics courses.…”
Section: Introductionmentioning
confidence: 99%